Evaluation of MSME Performance in Pontianak: An Institutional Perspective - Muhammad Zalviwan; Windi Pratiwi; Uray Andrey Indra Maulana (Dinasti Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a crucial pillar of the Indonesian economy. While the city of Pontianak possesses substantial potential for MSME development, several challenges persist, notably within the institutional framework. This study aims to evaluate the performance of MSMEs in Pontianak, specifically from an institutional perspective. Employing a big data approach, this research analyzes MSME performance across various dimensions, including productivity, efficiency, innovation, and competitiveness. Prior research indicates that MSME performance in Pontianak is not yet optimal, which is attributed to factors such as the low quality of human resources, limited access to financing, and regulatory impediments. This study adopts a quantitative methodology utilizing a survey-based approach. The population for this study comprises 1,840 MSME operators in Pontianak. A sample of 185 respondents was selected for data collection. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. Path analysis was primarily employed to examine the comparative strength of direct and indirect relationships between variables. The results demonstrate that external factors significantly impact innovation (p < 0.001). Internal factors also exhibit a significant effect on innovation (p < 0.05). External factors have a significant negative impact on performance (p < 0.001), whereas the effect of internal factors on performance is not statistically significant (p > 0.05). Furthermore, innovation mediates the effect of external factors on performance (p < 0.001), and also mediates the effect of internal factors on performance (p < 0.05). Innovation itself also significantly impacts performance (p < 0.001).